Influence of Vehicular Flow Instability in a Transport Network on Risk Reduction: Test in a Two-Link Network - Antonino Vitetta (Journal of Advanced Transportation)
It is important to study risk in transport systems because mobility is subject to probable dangerous events, both internal and/or external to the traffic flow. This paper presents a method for the probabilistic assessment of social risk for endogenous traffic flow events. The model specification considers the three components of occurrence, vulnerability, and exposure. The first two components, the effects deriving from phenomena endogenous to the flow are considered and specified as a function of mean speed to consider flow instability and vehicle energy. The third component is calculated based on the fundamental flow diagram. The aim is to integrate the specified models for occurrence and vulnerability assessment and the specified models for flow instability. This paper makes a novel contribution to the field by specifying possible occurrence and vulnerability functions, for estimating the probabilities deriving from events endogenous to the flow. The methodology is applied in a two-link road network, and the results obtained demonstrate the quality of the proposed model and the possibility of adequately modelling the phenomenon.